Tropical tropopause layer variability associated with the Madden-Julian oscillation during DYNAMO - Dagg, Erin L., author; Birner, Thomas, advisor; Johnson, Richard H., advisor; Schubert, Wayne H., committee member; Kirby, Michael, committee member (Colorado State University. Libraries, 2015)
As the transition region between the troposphere and stratosphere, the tropical tropopause layer (TTL) has importance as the gateway to the stratosphere for atmospheric tracers such as water vapor.  This has implications for Earth's radiative budget and climate.  Observations in this region show time variations across multiple scales that are not fully understood, including the intraseasonal variability of the Madden-Julian oscillation (MJO). In this study, we investigate the evolution of TTL properties and their vertical structure during the Dynamics of the Madden-Julian Oscillation (DYNAMO) field campaign from October-December 2011.  This time period is particularly interesting in that two prominent MJO passages were seen over the tropical Indian Ocean.   We focus analysis on two equatorial sites.  Gan Island, Maldives (0.7° S, 73.2° E) provides a better understanding of the response of the TTL to MJO dynamics in the region of initiation.  Manus Island, Papua New Guinea (2.1° S, 147.4° E) observations portray a later stage of the MJO during its eastward propagation.  We use multiple datasets, including high vertical resolution, three-hourly atmospheric soundings over the three-month period.  CALIPSO satellite data is additionally used in determining the presence of thin cirrus clouds and their impact on radiative heating rates.  Characteristics of the broadscale structure of the MJO are analyzed, as well as higher-frequency variations of the flow near the TTL accompanying an increase in MJO-related deep convective clouds. Spectral filtering is used to isolate low-frequency variability, Kelvin wave activity, and higher-frequency gravity wave perturbations.  A 7-20 day bandpass of the temperature and zonal wind fields reveals strong Kelvin wave signals in late October and early December.  This Kelvin wave response to large-scale convection exhibits a downward phase velocity consistent with an eastward-propagating energy source below.  The descending cold phase between 100-150 hPa coincides with a lowering of the cold point tropopause and an increase in cirrus cloud frequency preceding the active phase of the MJO.  The wave signals dissipate before reaching Manus Island, suggesting that the MJO may have decoupled from convection.  Further analysis shows lower stratospheric gravity wave activity does not appear to be modulated by the MJO, but is generally stronger at Manus Island due to its proximity to the west Pacific warm pool.
Keywords: Kelvin wave; tropical tropopause layer; DYNAMO; Madden-Julian oscillation